Silica particles with fluorescein-labelled cores for evaluating accessibility through fluorescence quenching by copper. Issue 22 (4th October 2021) - Gallagher, Samuel H.; Schlauri, Paul; Cesari, Emanuele; Durrer, Julian; Brühwiler, Dominik
Abstract : Silica particles with a fluorescent core were used to evaluate the accessibility of the core in function of the shell architecture. Abstract : Core–shell particles with fluorescent cores were synthesised by growing silica shells on fluorescein-labelled Stöber-type particles. The porosity of the shell could be altered in a subsequent pseudomorphic transformation step, without affecting the particle size and shape. These core–shell particles constitute a platform for the evaluation of pore connectivity and core accessibility by observing the effect of a quencher on the fluorescence signal emitted by the fluorescein-labelled cores. In combination with argon sorption measurements, quenching experiments with copper provided valuable information on the porosity generated during the shell formation process. It was further observed that the introduction of well-defined mesopores by pseudomorphic transformation in the presence of a structure-directing agent reduces the core accessibility. This led to the conclusion that the analysis by conventional gas sorption methods paints an incomplete picture of the mesoporous structure, in particular with regard to pores that do not offer an unobstructed path from the external particle surface to the core.